Culture & truth : the remaking of social analysis - Rosaldo, Renato (Boston : Beacon Press, 1989)
1. Ethology--Philosophy 2. Subjectivity 3. Discourse analysis,narrative 4. Ritual 5. Bereavemont
Faculty
Keywords: Ethnology -- Philosophy; Subjectivity; Discourse analysis, Narrative; Ethnology -- Methodology